2013
DOI: 10.1111/ceo.12254
|View full text |Cite
|
Sign up to set email alerts
|

Effect of phacoemulsification on trabeculectomy function

Abstract: Phacoemulsification performed after trabeculectomy significantly increased rates of bleb failure in the following 12 months but not at 24 months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 34 publications
(72 reference statements)
0
24
0
2
Order By: Relevance
“…Other studies have reported, after 2 years of follow-up, a failure (with need of topical medical therapy) in 29-45% of the eyes treated by a TE without AM, [2][3][4][5][6][7] and in 18-24% of eyes that had received a TE with AM. In controls, after TE with AM, a failure was found in 4-7% of the eyes (Table 3).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Other studies have reported, after 2 years of follow-up, a failure (with need of topical medical therapy) in 29-45% of the eyes treated by a TE without AM, [2][3][4][5][6][7] and in 18-24% of eyes that had received a TE with AM. In controls, after TE with AM, a failure was found in 4-7% of the eyes (Table 3).…”
Section: Discussionmentioning
confidence: 96%
“…[1][2][3][4][5][6] However, a study showed that the rate of failure of TE after cataract surgery is not different from the natural course of TE. 7 The use of antimetabolites (AM) during TE reduced the failure rate; [8][9][10] also, the time between TE and cataract surgery 10,11 and baseline IOP 7 have been identified as factors affecting the outcome.…”
Section: Introductionmentioning
confidence: 99%
“…Trabeculectomy alone in these eyes has the disadvantage that future cataract extraction may result in loss of the functioning filter. 37,38 Nevertheless, trabeculectomy has a role in PACG eyes that have already undergone phacoemulsification and in eyes with clear lens. In the presence of a visually significant cataract, the surgical options to consider are phacoemulsification alone or combined phacotrabeculectomy.…”
Section: Combined Phacoemulsification and Trabeculectomy (Phacotrabecmentioning
confidence: 99%
“…In a retrospective study done by Nguyen et al [26] they found that phacoemulsification performed after trabeculectomy significantly increased rates of bleb failure in the following 12 months, but not at 24 months.…”
Section: Discussionmentioning
confidence: 99%